Development of Recycled Style Sandals at the Youth Organization Community, Bojonghaleuang Village, West Bandung Regency - Wenny Anggraini Natalia; Tan Indra Janti; Lois Denissa; Junnica Hakim Santoso; Ayu Kartika Sari; Jesslyn Ivana Kristi (Journal of Innovation and Community Engagement, 2022)
This community empowerment activity was implemented at the initiative of the Karang Taruna community in Bojonghaleuang Village, West Bandung Regency. This activity was intended to provide briefing and creativity training for youth organizations so that they would develop creativity that can be developed into commodity product businesses that are needed by the community. Garment scraps, leftover production and sorting/rejects that are abundant in the city of Bandung require community cultivation. The method used was the cooperative demonstration and practical making of decorative sandals, following modules that were taught both online and onsite, and applied in practice. Then, the youth group can re-explore the sandal model in another form that is more attractive, according to creativity, and can then meet market tastes. This training has many benefits, namely developing youth creativity, increasing the value of the benefits of leftover fabrics or rejected products into commodities of economic value. The utilization of textile waste as a self-supporting commodity for Karang Taruna really helps improve environmental sustainability in the city of Bandung. As a result of this activity, the Karang Taruna community was very enthusiastic about doing the exercises, able to produce interesting sandal creations, even some youth organizations have received purchase orders from the surrounding community.